Editorial. (1st July 2019) - Green, Sarah; Laviolette, Patrick
Abstract : When we started our four‐year tenure as co‐editors of SA/AS in 2015, one of our missions was to help satisfy the high demand from EASA's membership to publish more special issue content. At the same time, we were also committed to keeping enough free space for the classic independent research article, as well as to foster interactive debates and special short forum discussions. The solution we found to meet the increasing call for thematic focused issues while giving adequate space to all the other forms of contribution was to introduce up to two online‐only special issues per year.